1994
DOI: 10.1016/0006-8993(94)90312-3
|View full text |Cite
|
Sign up to set email alerts
|

Visual wulst influences on flash evoked responses in the ectostriatum of the zebra finch

Abstract: Anatomical data suggest that visual information from the thalamofugal pathway contributes to visual processing in the tectofugal pathway. We addressed the question of the functionality of anatomically described connections to the visual system of a laterally eyed bird, the zebra finch. The study shows the contribution of visual wulst efferents to visual processing in the ectostriatum by recordings of visually evoked slow field potentials. Suppression of visual wulst activity resulted in a selective reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The sensory modalities of these groups of neurons and their c‐fos activity pattern would also indicate a similar response to certain behavioral situations. This connection has been found in zebra finches, in which the ectostriatum integrates information from the thalamofugal pathway (Engelage and Bischof, 1994; Bischof and Watanabe, 1997). The LNH does receive a moderate projection from the HAD (Sadananda and Bischof, 1997), which other studies (Shimizu and Karten, 1995) also support, an indicator that the visual wulst modulates tectofugal processing.…”
Section: Discussionmentioning
confidence: 67%
“…The sensory modalities of these groups of neurons and their c‐fos activity pattern would also indicate a similar response to certain behavioral situations. This connection has been found in zebra finches, in which the ectostriatum integrates information from the thalamofugal pathway (Engelage and Bischof, 1994; Bischof and Watanabe, 1997). The LNH does receive a moderate projection from the HAD (Sadananda and Bischof, 1997), which other studies (Shimizu and Karten, 1995) also support, an indicator that the visual wulst modulates tectofugal processing.…”
Section: Discussionmentioning
confidence: 67%
“…Figure 3 shows representative recordings from central parts of the investigated structures. Complete recording tracks are not provided here, as these have been depicted in previ ous publications [Engelage and Bischof, 1988;Engelage and Bischof, 1989;Bredenkotter and Bischof, 1990a] trials, ipsilateral VEPs are substantially enhanced in white birds, reaching the amplitudes of the contralateral response in some cases ( fig. 3B).…”
Section: Electrophysiological Resultsmentioning
confidence: 99%
“…In previous experiments we showed that ipsilateral stimulus processing is especially subject to severe inhibition [Engelage and Bischof, 1988;Brcdenkotter and Bischof, 1990a]. All recordings from white zebra finches show increased amplitudes of ipsilateral VEPs and therefore indicate a reduced inhibition of ipsilateral stimulus processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations